Workplace occupation and the possibilities of popular power in Chile and Argentina, 1972–6. Issue 4 (7th June 2019) - Fishwick, Adam
ABSTRACT: The recent wave of occupations has had a transformative effect on radical politics, but, to date, many have been restricted in their social and spatial expansion. Reflecting on these challenges, this article examines workplace occupation in the coordinadoras interfabriles in Argentina (1975–6) and the cordones industriales in Chile (1972–3) to understand how they overcame barriers to such expansion. Starting from debates in critical geography and social movement studies on space and occupations, I unpack the possibilities for popular power that emerged in this period by using approaches from critical labour studies and autonomist Marxism. First, I outline the generative role of the workplace in producing these possibilities in a context of wider social change. Second, I demonstrate how the capacity for expansion lay in the simultaneous capacity to disrupt and reconstruct social relations derived from solidarities that exceeded the existing physical space of occupation.